(untitled) - Huỳnh, Thị Mỹ Duyên (Cần Thơ, 2017)
This coursebook aims to help students acquire basic vocabulary knowledge of pharmacy, the information conceming drugs and prescriptions.
Keywords: Pharmacy,Dược; Terminology,Thuật ngữ